Percepção materna do estado nutricional e qualidade da dieta : um estudo com escolares de 7-10 anos - Arpini, Luana da Silva Baptista (2013)
This is a dissertation about maternal perception of the child's nutritional status, structured in three manuscripts. The first manuscript is a systematic review of the literature whose objective is to investigate the relationship between maternal perception of the child’s body weight and infant feeding. The results showed that the maternal perception influences the control feeding practices of infant, as well as the maternal preoccupation with child's body weight may be a factor mediating this association. The second manuscript, cross-sectional design, with 518 children 7-10 years, objective to study the correspondence between maternal perception (MP) and nutritional status (NS) of the schoolchildren of the Espírito Santo’s countryside. To analyse the relationship between MP and NS the adjusted kappa statistic (k) was used and the association of the predictors of MP were used the chi-square and Fisher's exact tests for univariate analysis and multinomial logistic regression for multivariate analyse. Results showed higher and lower concordance for thinness and obesity, respectively. 67 % of mothers perceived nutritional status of their children corresponding to classified by BMI, 30% underestimated and 3% overestimated the child's NS. Substantial concordance between MP and NS was found, and the male and maternal concern were associated factors. The third manuscript of the approach sectional, aimed to analyse the relationship between MP of the child’s NS as diet quality of a sample of 1788 students ( 1,272 of the Espírito Santo’s urban region and 516 of the rural region), coming from the projects "Vitória Health" and "Santa Maria de Jetibá Health". After quality control of databases, the chi - square test was used to determine differences in proportions between groups and multinomial logistic regression to adjust. In both regions, higher percentages of low-quality diet were found. Race /skin color (black / brown), socioeconomic class (C and D + E) and maternal education (low and intermediate) were associated with lower diet quality in this population. Concludes - if, in this manuscript, the socioeconomic determinants directly influence the quality of the diet of schoolchildren, however, was not association between the concordance of the maternal perception with the child's nutritional status's diagnosis.